Evaluating the need for real-name verification system in Malaysian internet content regulation - Daud, Mahyuddin (2015)
The Real Name Verification System (RNVS) is an online web technology first introduced in South Korea. Introduced through amendment of the Act on Promotion of Information and Communications Network Utilization and Information Protection (CNA) in January 2007, Korean Internet users were legally required to verify personal identity using national registration numbers. Among others, it empowered the President of Korea to issue decree to any service providers serving on average 100,000 visitors per day to verify user identity through Korean national identification numbers323. Internet users who refuse to disclose their identity shall prohibit them from posting comments on popular websites - such as YouTube - whom applied RNVS requirements (Kim, 2008). While RNVS offered great assistance to law enforcement to quickly identify possible offenders, it however invited significant online security risks to Korean Internet users as all their personal details could be misused by irresponsible parties. This paper seeks to consider suitability of RNVS to be implemented in Malaysia to combat against massive availability of illegal and harmful content on the Internet. It shall be argued that RNVS is not suitable for Malaysian Internet content regulation for legal and technological barriers we need to encounter.